A reliable and reproducible protocol for sound-evoked vestibular myogenic potentials in rattus norvegicus - Raciti, Federica M.; Morales, Yasniary; Snapp, Hillary A.; Rajguru, Suhrud M. (Frontiers in Integrative Neuroscience, 2023)
Introduction Cervical vestibular evoked myogenic potentials (cVEMPs) provide an objective measure of the integrity of the sacculo-collic pathway leading to their widespread use as a clinical tool in the diagnostic vestibular test battery. Though the application of cVEMPs in preclinical models to assess vestibular function, as performed in relevant clinical populations, remains limited. The present study aimed to establish a rodent model of cVEMP with standardized methods and protocols, examine the neural basis of the responses, and characterize and validate important features for interpretation and assessment of vestibular function. Methods We compared air-conducted sound (ACS)-evoked VEMPs from the sternocleidomastoid muscles in naïve Brown Norway rats. A custom setup facilitated repeatable and reliable measurements which were carried out at multiple intensities with ACS between 1 and 16 kHz and over 7 days. The myogenic potentials were identified by the presence of a positive (P1)-negative (N1) waveform at 3–5 ms from the stimulus onset. Threshold, amplitude, and latency were compared with intensity- and frequency-matched responses within and between animals. Results cVEMP responses were repeatedly evoked with stimulus intensities between 50–100 dB SPL with excellent test-retest reliability and across multiple measurements over 7 days for all frequencies tested. Suprathreshold, cVEMP responses at 90 dB SPL for 6–10 kHz stimuli demonstrated significantly larger amplitudes (p < 0.01) and shorter latencies (p < 0.001) compared to cVEMP responses for 1–4 kHz stimuli. Latency of cVEMP showed sex-dependent variability, but no significant differences in threshold or amplitude between males and females was observed. Discussion The results provide a replicable and reliable setup, test protocol, and comprehensive characterization of cVEMP responses in a preclinical model which can be used in future studies to elucidate pathophysiological characteristics of vestibular dysfunctions or test efficacy of therapeutics.